Biofilm forming potential of Streptococcus suis: focusing on luxs/ai-2-mediated quorum sensing system - Tjokorda Istri Pramitasuri; Ni Made Adi Tarini; Ni Made Susilawathi; Anak Agung Raka Sudewi (Indonesian Archives and Biomedical Sciences, 2021)
Because of its virulence and ability to survive, the incidence of infection caused by Streptococcus suis (S. suis), an emerging zoonotic pathogen, is expected to increase significantly. A biofilm-forming process, which is a cornerstone of chronic infection, influences the survival rate of S. suis. The mechanism helps bacteria to live longer in host tissues, form colonies, escape immune clearance, and share genetic information. At this moment, the most studied regulatory mechanism of S. suis biofilm formation is Quorum Sensing (QS), mainly on LuxS/AI-2-mediated QS system, in which AI-2 is the most closely related molecule to biofilm formation. In this system, LuxS acts as the key player in the process. The understanding of biofilm formation in S. suis, especially the LuxS/AI-2-mediated QS system, is a valuable contribution to future therapeutic research frameworks.